Sistem Pendukung Keputusan Penilaian Kinerja Pegawai Menerapkan Metode COPRAS - Muhammad Andika Hasibuan (Bulletin of Information System Research, 2024)
PT. Nusira is a company engaged in the processing of crumb rubber. Crumb Rubber is a plantation trade that has a very important role in Indonesia. This trade can affect economic growth in Indonesia. In the process of improving the quality of work of each employee working at PT. Nusira, it is necessary to conduct an employee performance assessment. In assessing employee performance, a decision support system is needed. The method used in this study is the Complex Proportional Assessment (COPRAS) method using Rank Order Centroid (ROC) weighting. The COPRAS method is a method that can assume direct and proportional dependence of the level of significance and utility of existing alternatives with conflicting criteria, while ROC weighting is used to assign weight values ​​to each criterion. From the calculation of the COPRAS method with ROC weighting, a ranking is obtained in assessing employee performance at PT. Nusira must meet the above criteria by getting the highest score, then the one with the best employee performance is Alternative A2 on behalf of "Suwito" = 100.